A Finnic holy word and its subsequent history - Koski, Mauno (Scripta Instituti Donneriani Aboensis, 1990)
This article concentrates on a specific ancient holy word in Finnish and its subsequent development, hiisi. In the Finnish language region hiisi appears as an element in place names in over 230 villages established by the end of the thirteenth century, and at least a majority of these must have existed since prehistoric times. In Finland as well as in Estonia it is possible to demonstrate an earlier sacral function in places which contain hiisi as a component of their name, partly with the help of archeological discoveries, and partly with the help of oral folk tradition. It is particularly among the earliest settlement areas of Southwest Finland, Satakunta and Häme that hiisi features in the names of sacrificial sites or trees, in other words in the same areas where it features in the names of burial grounds. Names in which the hiisi element precedes a word meaning a lake, pond, or other water formation, occur particularly in the eastern Finnish dialect regions, as well as in the regions of Karelian, Olonets, Lydian, and Vepsian. In addition to its factual meaning of cult place, the Finnish word hiisi has come to denote a supernatural entity both in terms of its reference to a place and in terms of its reference to a being.